The relationship between distributed leadership and teacher innovativeness: Mediating roles of teacher autonomy and professional collaboration - Lin, Qi (Frontiers in Psychology, 2022)
Principals’ distributed leadership plays a critical role in teacher innovativeness; however, research evidence regarding the relationship between them is limited. This study aims at examining the effect of distributed leadership on teacher innovativeness as well as the mediating roles of teacher autonomy and professional collaboration. Using the data of 132,376 teachers derived from the 2018 Teaching and Learning International Survey (TALIS), the study applied a structural equation model (SEM) for analysis. The results revealed that distributed leadership had positive direct effects on teacher innovativeness, teacher autonomy, and professional collaboration. Meanwhile, teacher autonomy and professional collaboration significantly mediated the effect of distributed leadership on teacher innovativeness, respectively. Practical implications are discussed, school leaders are expected to adopt distributed leadership style and establish a supportive school environment, and individual teachers are supposed to cultivate a culture of collectivism and make effective use of autonomy in their teaching innovation.